(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the diversity and ecological role of Pelecaniformes within the Nandur Madhyameshwar Wetland, a Ramsar site of high conservation value in Maharashtra, India. Wetlands serve as dynamic ecosystems, critical for biodiversity and ecosystem stability through nutrient cycling, hydrological regulation, and support for various trophic interactions. Pelecaniformes comprising herons, ibises, and pelicans are essential avifaunal groups within these habitats, acting as bioindicators due to their sensitivity to water quality, habitat change, and resource availability. This research documents the species composition, population dynamics, and habitat preferences of Pelecaniformes in the Nandur Madhyameshwar Wetland, highlighting their roles in sustaining ecosystem resilience through nutrient cycling and fish population control. By examining key trophic and ecological interactions, this study underscores the necessity of wetland conservation to safeguard these keystone species and their ecological functions. Findings contribute valuable insights into avian diversity, emphasizing the importance of maintaining wetland integrity amid escalating anthropogenic pressures.